24th European Microwave Conference, 1994 1994
DOI: 10.1109/euma.1994.337298
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Melting-Snow Layer Attenuation and Scattering on Microwave Communication Links

Abstract: The presence of the melting-snow layer has significant effects on propagation in two respects, which should be considered in the design of microwave satellite and terrestrial communication links. Namely, these are excess attenuation and enhanced scattering. In this paper, the factors involved in the evaluation of attenuation and scattering due to melting layer presence are presented and analyzed. The results of this analysis are applied to two existing experimental links.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Besides the abrupt change in reflectivity, the melting layer usually produces a distinct polarimetric signature (Brandes & Ikeda, 2004;Giangrande et al, 2008;Trömel et al, 2014). It also frequently attenuates radio signals from radars and between telecommunication links (ITU-R P. 530-16, 2015;Kharadly & Hulays, 1994;Klaassen, 1990); this effect is particularly significant if the beam is nearly horizontal and consequently must travel long distances inside the melting layer (von Lerber et al, 2015). The melting layer attenuation and emission can also cause biases in precipitation estimation with radars (Bellon et al, 1997;Matrosov, 2008;Pujol et al, 2012;Zhang et al, 1994) and passive microwave radiometers (Battaglia et al, 2003;Bauer et al, 1999;Olson et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Besides the abrupt change in reflectivity, the melting layer usually produces a distinct polarimetric signature (Brandes & Ikeda, 2004;Giangrande et al, 2008;Trömel et al, 2014). It also frequently attenuates radio signals from radars and between telecommunication links (ITU-R P. 530-16, 2015;Kharadly & Hulays, 1994;Klaassen, 1990); this effect is particularly significant if the beam is nearly horizontal and consequently must travel long distances inside the melting layer (von Lerber et al, 2015). The melting layer attenuation and emission can also cause biases in precipitation estimation with radars (Bellon et al, 1997;Matrosov, 2008;Pujol et al, 2012;Zhang et al, 1994) and passive microwave radiometers (Battaglia et al, 2003;Bauer et al, 1999;Olson et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Examples 1, 5 and 6 are the simulations under the maximum rain rates of 10 mm/h, 30 mm/h and 50 mm/h with a triangular rain-cloud cell. The typical value 30 mm/h is chosen because the melting layer, the region where the precipitation changes from snow to rain, exists at lower rain rates, approximately below 30 mm/h [30]. Furthermore, the result has shown that the simulation result using this method is also in good agreement with the given one.…”
Section: Discussionmentioning
confidence: 81%